(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The work provides information that the thyroid gland can change its structure and volume under the influence of various factors, primarily during hormonal changes - puberty, menopause. It is shown that the manifestation of clinical signs of changes in the thyroid gland is diverse, where the cardiovascular system suffers first.